2003
DOI: 10.1097/00024720-200308000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Testing of an Artificial Cervical Joint and an Anterior Cervical Plate

Abstract: An in vitro biomechanical study was conducted to determine the effects of fusion and nonfusion anterior cervical instrumentation on cervical spine biomechanics in a multilevel human cadaveric model. Three spine conditions were studied: harvested, single-level artificial cervical joint, and single-level graft with anterior cervical plate. A programmable testing apparatus was used that replicated physiologic flexion/extension and lateral bending. Measurements included vertebral motion, applied load, and bending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(69 citation statements)
references
References 25 publications
3
64
2
Order By: Relevance
“…Contrary to a number of biomechanical studies previously published [16][17][18], we did not find that implantation of TDR at 1 or 2 levels could restore completely native kinematics of the cervical spine. We noted that ROM after TDR was systematically reduced for the three loading conditions, especially in AR and LB, even if the difference was not always significant.…”
Section: Instrumented Levelscontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to a number of biomechanical studies previously published [16][17][18], we did not find that implantation of TDR at 1 or 2 levels could restore completely native kinematics of the cervical spine. We noted that ROM after TDR was systematically reduced for the three loading conditions, especially in AR and LB, even if the difference was not always significant.…”
Section: Instrumented Levelscontrasting
confidence: 99%
“…They proposed resection of uncinates to restore the extent of 3D motions more completely. In fact, although some authors reported no difference in ROM between intact and instrumented spines [16][17][18], we noted that ROM in some of these studies was most often reduced but the difference was not statistically significant. As an example, Puttlitz et al [17] tested six human cervical spines intact and instrumented with TDR (ProDisc-C, Synthes) by applying 3D pure moments of 1 N m. ROM of instrumented spines was measured to 73 and 72% of intact spines in AR and LB, respectively; however, the authors concluded that there was no difference between the two tested conditions because difference was no statistically significant.…”
Section: Instrumented Levelscontrasting
confidence: 75%
See 1 more Smart Citation
“…Concerns regarding these issues led to the design and development of the cervical disc arthroplasty. Compared with anterior cervical discectomy and fusion, the cervical disc arthroplasty offers the theoretical biomechanical advantage of preservation of motion at the index level, which reduces stresses at the adjacent levels [12,13]. The equivalency or superiority of the cervical disc arthroplasty as an alternative to anterior cervical discectomy and fusion has been seen in FDA Investigational Device Exemption and other studies [5,7,8,10,22,30,32,34,35,37,38,[42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…The cervical disc arthroplasty is designed to maintain disc space height and motion at the index segment and prevent abnormal loading stresses and motion at adjacent segments that theoretically lead to accelerated degeneration [12,13]. During the past decade, the cervical disc arthroplasty has emerged as an alternative to fusion and has been shown to provide the pain relief and functional improvements similar or superior to those of anterior cervical discectomy and fusion in FDA Investigational Device Exemption clinical trials [5,8,10,22,30,32,35,38,44].…”
Section: Introductionmentioning
confidence: 99%